Recent chemo‐/biosensor and bioimaging studies based on indole‐decorated BODIPYs. (10th November 2019) - Ozcan, Emrah; Kazan, Hasan Huseyin; Çoşut, Bunyemin
Abstract: BODIPY is an important fluorophores due to its enhanced photophysical and chemical properties including outstanding thermal/photochemical stability, intense absorption/emission profiles, high photoluminescence quantum yield, and small Stokes' shifts. In addition to BODIPY, indole and its derivatives have recently gained attention because of their structural properties and particularly biological importance, therefore these molecules have been widely used in sensing and biosensing applications. Here, we focus on recent studies that reported the incorporation of indole‐based BODIPY molecules as reporter molecules in sensing systems. We highlight the rationale for developing such systems and evaluate detection limits of the developed sensing platforms. Furthermore, we also review the application of indole‐based BODIPY molecules in bioimaging studies. This article includes the evaluation of indole‐based BODIPYs from synthesis to characterization and a comparison of the advantages and disadvantages of developed reporter systems, making it instructive for researchers in various disciplines for the design and development of similar systems.